## Trending News

Promoted

# Solving systems using substitution and linear equations?

2x+y=-1

y=3x-16

How would I do then substitution?

### 2 Answers

Relevance

- 8 years agoFavorite Answer
first solve for y in the first equation

y=-2x-1

Now plug in this value of y in the first equation into the second equation

3x-16=-2x-1

-15=x

Now plug in this value of x into one of the equations

2(-15)+y=-1

-30+y=-1

y=29

- FredLv 78 years ago
Solve your 1st eqn for y. y = -1 -2x. Now substitute that value of y into your 2nd eqn.

-1-2x = 3x-16. Solve for x. Now that you have x put that back in either eqn to find y. Cake. :)

Still have questions? Get your answers by asking now.